Rich and pretty - Alam, Rumaan (Ecco, an imprint of HarperCollins Publishers, 2016)
This irresistible debut, set in contemporary New York, provides a sharp, insightful look into how the relationship between two best friends changes when they are no longer coming of age but learning how to live adult lives. As close as sisters for twenty years, Sarah and Lauren have been together through high school and college, first jobs and first loves, the uncertainties of their twenties and the realities of their thirties. Sarah, the only child of a prominent intellectual and a socialite, works at a charity and is methodically planning her wedding. Lauren beautiful, independent, and unpredictable is single and working in publishing, deflecting her parents worries and questions about her life and future by trying not to think about it herself. Each woman envies and is horrified by particular aspects of the other's life, topics of conversation they avoid with masterful linguistic pirouettes. Once, Sarah and Lauren were inseparable; for a long a time now, they ve been apart. Can two women who rarely see one other, selectively share secrets, and lead different lives still call themselves best friends? Is it their abiding connection or just force of habit that keeps them together? With impeccable style, biting humor, and a keen sense of detail, Rumaan Alam deftly explores how the attachments we form in childhood shift as we adapt to our adult lives and how the bonds of friendship endure, even when our paths diverge.